The guide to community preventive services what works to promote health? - Zaza, Stephanie; Briss, Peter A.; Harris, Kate W.; Task Force on Community Preventive Services (U.S.) (New York ; Oxford : Oxford University Press, 2005)
A primary resource to improve health and prevent disease in states, communities, community organizations, businesses healthcare organizations, and schools, this volume examines the effectiveness and efficiency of interventions to combat risky behaviours.
Includes bibliographical references.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Community health services -- United States; Preventive health services -- United States